2013
DOI: 10.1177/1077546313492182
|View full text |Cite
|
Sign up to set email alerts
|

An alternative scheme to reduce torque ripple and mechanical vibration in direct torque controlled permanent magnet synchronous motor

Abstract: The direct torque control (DTC) technique of a permanent magnet synchronous motor (PMSM) has received increasing attention due to its simplicity and robust dynamic response compared with other control techniques. The classical switching table based DTC presents large flux, torque ripples and more mechanical vibrations in the motor. Several studies have been reported in the literature on classical DTC. However, the studies that actually discuss or evaluate the classical DTC are limited. This paper proposes, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…The comparison with previous methods is given in terms of the average commutation frequency, per unit flux ripple “ Ψ ripple ”, and per unit torque ripple “ T ripple ”. Flux and torque ripples are calculated using the formula given in () [11], while per unit values of the torque ripple and the flux ripple for different methods are calculated as given in (): lefttrueψitalicripple=1Nfalse∑n=1N()ψs()nψref2Titalicripple=1Nfalse∑n=1N()Te()nTref2, lefttrueψitalicrippleitalicpu=ψitalicripplemethodAψitalicrippleBasicDTCofmethodATitalicrippleitalicpu=TitalicripplemethodATitalicrippleBasicDTCofmethodA. …”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison with previous methods is given in terms of the average commutation frequency, per unit flux ripple “ Ψ ripple ”, and per unit torque ripple “ T ripple ”. Flux and torque ripples are calculated using the formula given in () [11], while per unit values of the torque ripple and the flux ripple for different methods are calculated as given in (): lefttrueψitalicripple=1Nfalse∑n=1N()ψs()nψref2Titalicripple=1Nfalse∑n=1N()Te()nTref2, lefttrueψitalicrippleitalicpu=ψitalicripplemethodAψitalicrippleBasicDTCofmethodATitalicrippleitalicpu=TitalicripplemethodATitalicrippleBasicDTCofmethodA. …”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
“…In Table 5, the results presented by [11] were conducted with a load of 3 Nm; it can be observed that there is no significant reduction in either torque ripple or flux ripple. In addition, the presented waveform of the torque performance in [11] suffers from serious fluctuations when the motor is loaded. The authors in [13, 14] succeed in reducing both torque and flux ripples compared to the traditional DTC.…”
Section: Simulation and Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPWM by its nature creates harmonics as cluster at switching frequency and its multiples. These carrier frequency harmonics are of dominant in magnitude and create mechanical vibration in the drive [37]. A host of PWM methods, named, RPWM have been researched and proved for distribution of harmonic power.…”
Section: Vsi With Fluctuating DC Input and Motivationmentioning
confidence: 99%
“…8 A wellperforming motor can also help attenuate system vibration. 9,10 However, there is very limited published work available on the active control of driveline vibration of the Ravigneaux planetary power-split HEVs. Furthermore, most methods mainly focus on the vibration problems in EVs or conventional sedans instead of those in HEVs.…”
Section: Introductionmentioning
confidence: 99%